ANALISIS FAKTOR-FAKTOR FUNDAMENTAL YANG MEMPENGARUHI RISIKO SISTEMATIS SEBELUM DAN SELAMA KRISIS MONETER - Doddy Setiawan (Journal of Indonesian Economy and Business (JIEB), 2004)
This research investigates the issue of relationship between fundamental variables: asset growth, liquidity, leverage, total asset turn over and return asset, and systematic risk (beta) at two periods: before and after monetary crisis. The objectives of this research are: (1) to examine the effect of fundamental variables to systematic risk and (2) to examine the effect of monetary crises on systematic risk. The samples of this research are: 56 manufacture firms for before monetary crisis period and 105 manufacture firms for after monetary crisis period. The analysis shows that before monetary crises asset growth, total asset turn over and return on investment affect beta significantly. But, after monetary crisis period only leverage variable affect beta significantly. Based on these results investor can use fundamental variables to analyse systematic risk. This research also shows systematic risk before and after monetary crises are different. The results of this research confirm Ahmed and Lockwood (1998) that systematic risk is different in different economics condition.